علاقة الاسلوب الترفيهي بالعملية التعلمية في برامج الإذاعة الجزائرية - بطينة,فاطمة الزهرة; خالدي,فاطمة الزهراء; زين,شروق (University of Eloued جامعة الوادي, 2024)
جاءت هذه الدراسة لتسلط الضوء على علاقة الأسلوب الترفيهي بالعملية التعليمية في برامج الإذاعة الجزائرية، حيث نسعى في هذه المذكرة إلى تقييم مدى فعالية استخدام الأسلوب الترفيهي في تعزيز التعليم لدى الأساتذة المستمعين، وتحديد العوامل التي تساهم في نجاحه، وقد تم معالجة إشكالية الدراسة من خلال طرح التساؤل التالي: ما علاقة الأسلوب الترفيهي بالعملية التعليمية في برامج الإذاعة الجزائرية؟ وكان الهدف من هذه الدراسة هو معرفة عادات وأنماط التعرض للبرامج الإذاعية، كذلك التعرف على الدوافع وراء استخدام الأسلوب الترفيهي في العملية التعليمية في برامج الإذاعة الجزائرية ، وأيضا مدى مساهمة هاته البرامج في نجاح العملية التعليمية من خلال أسلوبها الترفيهي. أما عن الإجراءات المنهجية المعتمدة تندرج دراستنا ضمن الدراسات المسحية ، حيث اعتمدنا على المنهج المسحي، أما بالنسبة لعينة الدراسة فشملت أساتذة التعليم الطور الابتدائي لولاية الوادي، وتم تحديد 100 مفردة بحثية، أما الأدوات المستخدمة في الدراسة اعتمدنا على أداة الاستمارة كأداة رئيسية تم توزيعها على عينة الدراسة، بالإضافة إلى أداة الملاحظة في الدراسة الميدانية، وهذه الأخيرة تم تطبيقها على عينة قصدية غير عشوائية من طرف أساتذة مستمعين للبرامج الإذاعية، وقد توصلت الدراسة إلى نتائج أساسية وهي ما يلي: - توصلت الدراسة إلى أن أفراد العينة يتعرضون إلى البرامج الإذاعية - توصلت الدراسة إلى ان من أسباب التعرض للبرامج الإذاعية هو اخذ فكرة على هاته البرامج وإذا كانت تأتي بثمارها فيوظفها الأستاذ في التعليم. - توصلت الدراسة أن من أهداف أفراد عينة الدراسة من وراء استخدام الأسلوب الترفيهي في العملية التعليمية هو توعية التلاميذ وتشجيع روح المنافسة بينهم. - توصلت الدراسة إلى أن استخدام الأسلوب الترفيهي في العملية التعليمية مع التلاميذ فعال في تحقيق نتائج مرضية. Summary: This study came to shed light on the relationship of the entertainment method to the educational process in Algerian radio programmes. In this memorandum, we seek to evaluate the effectiveness of using the entertainment method in enhancing education among listening teachers, and to identify the factors that contribute to its success. The problem of the study was addressed by presenting Next question: What is the relationship of the entertainment style to the educational process in Algerian radio programs? As for the methodological procedures adopted, our study falls within the survey studies, as we relied on the survey method. As for the study sample, it included primary education teachers in the state of El Oued, and 100 research items were identified. As for the tools used in the study, we relied on the questionnaire tool as the main tool that was distributed to a sample. The study, in addition to the observation tool in the field study, was applied to a non-random, intentional sample by professors listening to radio programs. The study reached basic results, which are the following: The study found that sample members are exposed to radio programs The study concluded that one of the reasons for exposure to radio programs is to have an idea for these programs, and if they bear fruit, the professor uses them in teaching. The study concluded that one of the goals of the study sample members behind using the entertainment method in the educational process is to educate students and encourage the spirit of competition among them. The study concluded that using the entertainment method in the educational process with students is effective in achieving satisfactory results
Keywords: العملية التعليمية; البرامج; entertainment; educational process